Borges and the brain: Visible connections with Neurocognitive Linguistics - Gil, Jose Maria (2013)
Neuroscientists have obtained vast and deep knowledge of the physical structures in the brain. Nevertheless, this knowledge is far from revealing HOW the brain performs the processes used to produce and understand utterances. For example, the enormous and profitable development in modern brain imaging offers information about WHERE things are going on, but not about WHAT is going on. It is not hard to understand why neuroscientists will not provide the answers that linguists and philosophers are trying to find: Neuroscientists do not study linguistic evidence (and they do not need to do so). Thus it is not possible to understand how the brain processes language without understanding linguistics. On the basis of the complex evidence provided by neuroscience and linguistics, it is possible to build a bridge between neural networks and relational networks. After accounting for the strong affinities between neurocognitive linguistics and Borges's writings, we finally arrive at a surprising conclusion: we can learn something about the structure and operation of the brain not only from linguistics, but also from literature.